Near-Infrared Spectroscopy in Extremely Preterm Infants - Pavlek, Leeann R.; Mueller, Clifford; Jebbia, Maria R.; Kielt, Matthew J.; Fathi, Omid (Frontiers in Pediatrics, 2021)
With advances in neonatal care, survival of premature infants at the limits of viability has improved significantly. Despite these improvement in mortality, infants born at 22 to 24 weeks gestation are at a very high risk for short- and long-term morbidities associated with prematurity. Many of these diseases have been attributed to abnormalities of tissue oxygenation and perfusion. Near-infrared spectroscopy utilizes the unique absorption properties of oxyhemoglobin and deoxyhemoglobin to provide an assessment of tissue regional tissue oxygen saturation, which can be used to calculate the fractional tissue oxygen extraction. This allows for a non-invasive way to monitor tissue oxygen consumption and enables targeted hemodynamic management. This mini-review provides a brief and complete overview of the background and physiology of near-infrared spectroscopy, practical use in extremely preterm infants, and potential applications in the neonatal intensive care unit. In this mini-review, we aim to summarize the three primary application sites for near-infrared spectroscopy, disease-specific indications, and available literature regarding use in extremely preterm infants.